Spectrum Of IHC P16 Expression In Epithelial Ovarian Tumors And Its Correlation With Histological Grading - Haque, Nida; Devra, Anshu Gupta; Gupta, Vatsala; Kalonia, Tushar; Verma, Jaykiran (Journal of Neonatal Surgery, 2025)
Introduction- Neoplastic ovarian disorders originate from three main cell types: (1) müllerian epithelium, (2) germ cells, and (3) sex cord–stromal cells. The WHO classifies ovarian tumors, with most arising from müllerian epithelium, based on differentiation and proliferation. The three major histologic types are serous, mucinous, and endometrioid tumors. Aim: To study the spectrum of IHC p16 expression in epithelial ovarian tumors and its correlation with histological grading. Methodology: This cross-sectional study was conducted in a tertiary care medical centre in western Uttar Pradesh.It includes ovarian tumors received in department of pathology, diagnosed as surface epithelial tumors during time frame of 18 months. IHC p16 analysis was done and on the basis of staining expression, were categorised into three classes: Absent, heterogeneous or normal and block or strong positivity. The correlation between p16 expression patterns and tumor histological grade was statistically analyzed. Results: A total of 35 cases were analyzed, with the majority being serous tumors (77%), followed by mucinous tumors (20%) and one Brenner tumor. Among benign tumors, 83.3% exhibited heterogeneous p16 expression, whereas all high-grade carcinomas (100%) demonstrated strong p16 positivity. Low-grade carcinomas primarily showed heterogeneous expression, while borderline tumors displayed variable p16 staining. The correlation between p16 expression and tumor grading was statistically significant (p-value = 0.0033), suggesting a strong association between p16 expression and high-grade malignancies. Conclusion: This study highlights the diagnostic and prognostic significance of IHC p16 expression in epithelial ovarian tumors. The findings suggest that p16 overexpression is a hallmark of high-grade carcinomas, while benign and low-grade tumors predominantly retain normal p16 expression. These results reinforce the role of p16 as a valuable IHC marker for tumor grading and prognostic assessment in ovarian carcinoma.